Transformation of educational paradigms in the context of global changes: will digitized reputation become a strategic resource of the new world order? - Dunayev , Igor; Kasianchuk , Andrii; Zarutskyi , Oleksii (Pressing Problems of Public Administration, 2025)
The article explores the phenomenon of educational paradigm transformation under the influence of digitalization and artificial intelligence development, as well as the potential of tokenized reputation as an innovative mechanism for verification and capitalization of personal capital in the new world order. Based on systematic analysis, a fundamental crisis of traditional educational models has been identified, caused by the devaluation of structured information’s value due to its accessibility through AI systems. The study demonstrates that in conditions where the ability to reproduce knowledge loses its uniqueness, the development of multidimensional personal capital, including aspects inaccessible to algorithmic imitation, becomes particularly important. The concept of tokenized reputation is substantiated as a technological infrastructure for verification and capitalization of holistic personal potential, based on decentralized mechanisms of multiple attestations, overcoming the dichotomy between economically-oriented and holistic approaches to education. The research methodology combines historical-logical, systemic, and comparative approaches, employing both theoretical modelling and scenario analysis to conceptualize the tokenized reputation phenomenon and its implementation potential. This work represents the first comprehensive attempt to integrate blockchain technology principles with educational transformation theories in the context of global geopolitical cycles. A comparative analysis of various approaches to education modernization in digital transformation has been conducted, including AI-adaptive learning, micro-credential models, educational metaverses, communitarian approaches, as well as state-controlled digitalization, corporate ecosystems, and sovereign platforms. The potential of tokenized reputation as an integration mechanism capable of combining the advantages of different approaches and ensuring synergy of corporate and public education management transformations is revealed. Special attention is paid to the prospects of implementing the tokenized reputation concept in Ukraine for verification and capitalization of human potential in post-war reconstruction and European integration. A practical case of using decentralized information platforms to create a system for verifying the competencies of demobilized military personnel and youth studying abroad is proposed. The strategic importance of forming a national tokenized reputation infrastructure to ensure competitiveness in the new multipolar world order is substantiated.